Chicano Gangs/Chicana Girls: Surviving the "Wild" Barrio - Ibarraran Bigalondo, Amaia (Miscelánea: A Journal of English and American Studies, 2014)
The emergence and divulgation of a Chicana female identity is inevitably linked to the Chicana Movement, which favored the liberation and empowerment of the collective, long submitted to male dominance and social discrimination. Regardless the obvious achievements of the Movement in the personal and communal spheres, the situation of may US barrios is still far from being ideal, and Chicana adolescents are the victims of poor educational resources, high rates of teen pregnancy and a still overtly masculine domination. In this context, there is a big group of young Chicanas who opt for seeking empowerment and a voice by joining a collective that provides them with the visibility they lack within the mainstream society and their own group: the gang. The aim of this work is to show two different approaches to the same life situation, as portrayed in two contemporary Chicana novels, Locas (1997), by Yxta Maya Murray, and the autobiographical Two Badges: The Lives of Mona Ruiz (1997), in an attempt to expose the harsh situation these women have to endure today and the ways out/in the novels propose in such circumstances.
Keywords: Chicana literature; Female adolescentes; Barrio life; Gangs; Violence